2014
DOI: 10.2217/pgs.14.73
|View full text |Cite
|
Sign up to set email alerts
|

CYP2B6 Genotype, but not Rifampicin-Based Anti-TB Cotreatments, Explains Variability in Long-Term Efavirenz Plasma Exposure

Abstract: Plasma efavirenz exposure is mainly influenced by CYP2B6 genotype, but not by rifampicin cotreatment. Therefore, no efavirenz dosage adjustment during rifampicin cotreatment is required in Ugandans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
17
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 44 publications
5
17
3
Order By: Relevance
“…Semvua et al reported a similar outcome in Tanzanian patients, although C max , C min , and AUC 0–24 were slightly but insignificantly lower during RIF cotreatment . No effects of RIF coadministration on plasma concentrations of EFV at C mid‐dose or C min were reported in Cambodian, South African, Thai, Ugandan, and Tanzanian patients . However, our finding is in disagreement with a recent report by Cho et al, who demonstrated a decrease in EFV exposure parameters with a corresponding increase in 8‐OH‐EFV on a single dose of EFV after 10 days of RIF pretreatment in healthy volunteers, and with an earlier report by López‐Cortés et al, who showed significant decreases in C max , C min , and AUC 0–24 in the presence of RIF coadministration…”
Section: Discussioncontrasting
confidence: 78%
“…Semvua et al reported a similar outcome in Tanzanian patients, although C max , C min , and AUC 0–24 were slightly but insignificantly lower during RIF cotreatment . No effects of RIF coadministration on plasma concentrations of EFV at C mid‐dose or C min were reported in Cambodian, South African, Thai, Ugandan, and Tanzanian patients . However, our finding is in disagreement with a recent report by Cho et al, who demonstrated a decrease in EFV exposure parameters with a corresponding increase in 8‐OH‐EFV on a single dose of EFV after 10 days of RIF pretreatment in healthy volunteers, and with an earlier report by López‐Cortés et al, who showed significant decreases in C max , C min , and AUC 0–24 in the presence of RIF coadministration…”
Section: Discussioncontrasting
confidence: 78%
“…Contradictory reports exist in the literature, though recent studies, including our noncompartmental PK and PK-pharmacodynamics (PD) relationship analyses reported on EFV using the same data, suggest the absence of a significant effect of a RIF-based anti-TB regimen (13,(31)(32)(33). The covariate analysis in the present study confirmed the absence of the effect of a RIF-based anti-TB regimen on the disposition of EFV and 8OHEFV.…”
Section: Discussionsupporting
confidence: 78%
“…PK models describing the disposition of efavirenz in plasma have been reported previously (3,(10)(11)(12)(13). A single study reported a PK model comprising both the parent drug (EFV) and the metabolite (8OHEFV) in plasma after a single dose that was lower than the recommended dose of efavirenz in 17 healthy Korean male subjects (14).…”
mentioning
confidence: 99%
“…[19][20][21][22][23][24] Moreover, the genes coding for theses enzymes and transporter proteins are genetically polymorphic displaying wide interethnic and interindividual variations in EFV, NVP or lumefantrine disposition. 23,[25][26][27][28][29] Concomitant ART and antimalarial drugs treatment is marred by drug-drug interactions involving inhibition and/or induction of drug-metabolizing enzymes or transporter proteins, whose extent may further be influenced by pharmacogenetics variations. As HIV treatment is life-long, long-term CYP3A induction by chronic use of EFV in HIV patients 22,30 may lower the plasma exposure of antimalarial drugs such as lumefantrine to cause treatment failure or drug resistance.…”
Section: Introductionmentioning
confidence: 99%